2019
DOI: 10.1017/cjn.2019.286
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative, Patient-Centered Assessment of Muscle Cramp Impact and Severity

Abstract: ABSTRACT:Background:There is an urgent need for new therapeutic options to treat muscle cramps; however, no patient-reported measures exist that capture the entire cramp experience. We conducted a qualitative study to assess the experience of patients suffering muscle cramps, aiming to understand what factors determine the impact cramps have in patients’ lives to guide the development of a patient-centered outcome measure of cramp severity and impact.Methods:We enrolled patients with cramps due to several etio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…These findings concur with other reports of the disruptive impact of leg cramps on patients' health and quality of life. [1][2][3][4][5]9 One disconcerting finding from our study, reported earlier by others, is that very few subjects discussed their leg cramps with their physicians. 1,2 Although there is limited definitive research investigating effective ways to mitigate leg cramps, 10,11 this lack of reporting suggests that clinicians may miss an opportunity to discuss the benefits and harms of potential treatment options with their patients.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…These findings concur with other reports of the disruptive impact of leg cramps on patients' health and quality of life. [1][2][3][4][5]9 One disconcerting finding from our study, reported earlier by others, is that very few subjects discussed their leg cramps with their physicians. 1,2 Although there is limited definitive research investigating effective ways to mitigate leg cramps, 10,11 this lack of reporting suggests that clinicians may miss an opportunity to discuss the benefits and harms of potential treatment options with their patients.…”
Section: Discussioncontrasting
confidence: 52%
“…There is no validated survey for leg cramps, hence the survey was developed by the researchers based on a literature review and similar questionnaires used in previous research. 1,3,7,9 It included demographic questions as well as those addressing overall health, physical activity, and sedentarism, as well as questions on the frequency, rest-or exercise-induced, duration, and site of leg cramps and their impact on the patient (Supplemental Appendix). Descriptive summary statistics were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Prevalence of muscle cramp ranges from 33%-95% in adults (Wilder 1940, Norris et al 1957, Hall 1947, Jansen et al 1990, Oboler et al 1991, Naylor and Young 1994, Abdulla et al 1999, Rubin 2018, Katzberg et al 2019, Murata et al 2019, Katz and Sadeghian 2019. Muscle cramps are particularly prevalent in those who are hypohydration, engaged in prolonged exercise, pregnant and older (Rubin 2018, Katz andSadeghian 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Muscle cramps are particularly prevalent in those who are hypohydration, engaged in prolonged exercise, pregnant and older (Rubin 2018, Katz andSadeghian 2019). From a clinical perspective, those who suffer from metabolic, neuromuscular, and neurological conditions, and those treated with beta-agonists, diuretics, and statins also suffer from muscle cramps (Rubin 2018, Katzberg et al 2019, Murata et al 2019, Katz and Sadeghian 2019. Muscle cramps are sudden, explosive, involuntary, and painful contractions of a muscle (or part of it), and are associated with the repetitive and abnormal firing of the innervating motor neurons (Minetto et al 2013).…”
Section: Introductionmentioning
confidence: 99%